The genomic consequences and persistence of sociality in spiders - Ma, Jilong; Bechsgaard, Jesper; Aagaard, Anne; Villesen, Palle; Bilde, Trine; Schierup, Mikkel Heide (Genome Research, 2025)
In cooperatively breeding social animals, a few individuals account for all reproduction. In some taxa, sociality is accompanied by a transition from outcrossing to inbreeding. In concert, these traits reduce effective population size, potentially rendering transitions to sociality “evolutionarily dead-ends.” We addressed this hypothesis in a comparative genomic study in spiders, in which sociality has evolved independently at least 23 times, but social branches are recent and short. We present genomic evidence for the evolutionary dead-end hypothesis in a spider genus with three independent transitions to sociality. We assembled and annotated high-quality, chromosome-level reference genomes from three pairs of closely related social and subsocial Stegodyphus species. We timed the divergence between the social and subsocial species pairs to be from 1.3 million to 1.8 million years. Social evolution in spiders involves a shift from outcrossing to inbreeding and from an equal to a female-biased sex ratio, causing severe reductions in effective population size and decreased efficacy of selection. We show that transitions to sociality only had full effect on purifying selection at 119, 260, and 279 kya, respectively, and follow similar convergent trajectories of progressive loss of diversity and shifts to an increasingly female-biased sex ratio. This almost deterministic genomic response to sociality may explain why social spider lineages do not persist. What causes species extinction is not clear, but either could be selfish meiotic drive eliminating the production of males or could be an inability to retain genome integrity in the face of extremely reduced efficacy of selection.
10.1101/gr.279503.124